Resting heart rate and incident atrial fibrillation: A stratified Mendelian randomization in the AFGen consortium. - J E Siland; B Geelhoed; C Roselli; B Wang; H J Lin; S Weiss; S Trompet; M E van den Berg; E Z Soliman; L Y Chen; I Ford; J W Jukema; et al. (PLoS ONE)
Background Both elevated and low resting heart rates are associated with atrial fibrillation (AF), suggesting a U-shaped relationship. However, evidence for a U-shaped causal association between genetically-determined resting heart rate and incident AF is limited. We investigated potential directional changes of the causal association between genetically-determined resting heart rate and incident AF. Method and results Seven cohorts of the AFGen consortium contributed data to this meta-analysis. All participants were of European ancestry with known AF status, genotype information, and a heart rate measurement from a baseline electrocardiogram (ECG). Three strata of instrumental variable-free resting heart rate were used to assess possible non-linear associations between genetically-determined resting heart rate and the logarithm of the incident AF hazard rate: <65; 65-75; and >75 beats per minute (bpm). Mendelian randomization analyses using a weighted resting heart rate polygenic risk score were performed for each stratum. We studied 38,981 individuals (mean age 59±10 years, 54% women) with a mean resting heart rate of 67±11 bpm. During a mean follow-up of 13±5 years, 4,779 (12%) individuals developed AF. A U-shaped association between the resting heart rate and the incident AF-hazard ratio was observed. Genetically-determined resting heart rate was inversely associated with incident AF for instrumental variable-free resting heart rates below 65 bpm (hazard ratio for genetically-determined resting heart rate, 0.96; 95% confidence interval, 0.94-0.99; p = 0.01). Genetically-determined resting heart rate was not associated with incident AF in the other two strata. Conclusions For resting heart rates below 65 bpm, our results support an inverse causal association between genetically-determined resting heart rate and incident AF.